Assessment and comparison of retention of zirconia copings luted with different cements onto zirconia and titanium abutments: An in vitro study - Neelima Sreekumar Menon; G P Surendra Kumar; K R Jnanadev; C L Satish Babu; Shilpa Shetty (Wolters Kluwer Medknow Publications, 2016)
Aim: The purpose of this in vitro study was to assess and compare the retention of zirconia copings luted with different luting agents onto zirconia and titanium abutments. Materials and Methods: Titanium and zirconia abutments were torqued at 35 N/cm onto implant analogs. The samples were divided into two groups: Group A consisted of four titanium abutments and 32 zirconia copings and Group B consisted of four zirconia abutments and 32 zirconia copings and four luting agents were used. The cemented copings were subjected to tensile dislodgement forces and subjected to ANOVA test. Results: Zirconia abutments recorded a higher mean force compared to titanium. Among the luting agents, resin cement recorded the highest mean force followed by zinc phosphate, glass ionomer, and noneugenol zinc oxide cement, respectively. Conclusion: Highest mean retention was recorded for zirconia implant abutments compared to titanium abutments when luted with zirconia copings.